Beneficial Relationships Between Endophytic Bacteria and Medicinal Plants - Wu, Wei; Chen, Wenhua; Liu, Shiyu; Wu, Jianjun; Zhu, Yeting; Qin, Luping; Zhu, Bo (Frontiers in Plant Science, 2021)
Plants benefit extensively from endophytic bacteria, which live in host plant tissues exerting no harmful effects. Bacterial endophytes promote the growth of host plants and enhance their resistance towards various pathogens and environmental stresses. They can also regulate the synthesis of secondary metabolites with significant medicinal properties and produce various biological effects. This review summarizes recent studies on the relationships between bacterial endophytes and medicinal plants. Endophytic bacteria have numerous applications in agriculture, medicine, and other industries: improving plant growth, promoting resistance towards both biotic and abiotic stresses, and producing metabolites with medicinal potential. Their distribution and population structure are affected by their host plant's genetic characteristics and health and by the ecology of the surrounding environment. Understanding bacterial endophytes can help us use them more effectively and apply them to medicinal plants to improve yield and quality.